Static analysis of a high arch dam - Ghafoori, Yaser (Acta hydrotechnica, 2019)
The paper presents the design and static analysis of a high arch dam. A feasibility study was conducted on the dam in the 90s and a preliminary layout was designed. However, the dams construction phase has been never started. In this paper, the design and layout of the dam under consideration are in accordance with the US manuals for the design of arch dams. The structures three-dimensional model was entered into the program SAP2000 and three-dimensional solid finite elements were used to discretize the model. This paper considers the hydrostatic pressure of the water reservoir and concrete self-weight. The analysis was performed for both the maximum and the minimum designed water level and for the case when the reservoir is empty. Special attention is given to the boundary conditions of the dam at its abutments and foundation. The results show that the planned layout is good for the dams construction. The arch dams curve transfers the loads to the abutments. The significant role of the foundation rigidity and the reservoir water level in the stress distribution and nodal displacements within the arch dam is observed.
Keywords: arch dam; civil engineering; displacement; finite element; gradbeništvo; hidrotehnika; hydrotechnics; končni elementi; ločna pregrada; napetosti; pomiki; static analysis; statična analiza; stress